2002
DOI: 10.1889/1.1827874
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective for the thermal degradation mechanism of blue BAM

Abstract: Abstract— A new thermal degradation mechanism for blue BAM (BaMgAl10O17:Eu2+) under thermal treatment in the presence of water is proposed. The water can be originated either from the thermal treatment steps, such as organic binder baking steps, or from the atmosphere under which blue BAM is being heated. Under such thermal treatment conditions, water molecules can be easily intercalated into the conduction layers of blue BAM, resulting in not only the depreciation of luminance but also in the emission color c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…2. Phosphor particles grown in the presence of LiCl and NH 4 Cl are nearly spherical where as particles grown in the presence of KCl and NaCl are plate like structure. When compared to a phosphor prepared without flux, the growth of particles in the presence of flux is high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Phosphor particles grown in the presence of LiCl and NH 4 Cl are nearly spherical where as particles grown in the presence of KCl and NaCl are plate like structure. When compared to a phosphor prepared without flux, the growth of particles in the presence of flux is high.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism involved in degradation and a green shift in BAM phosphor is not fully understood. [2][3][4][5][6] It is reported that the BAM with excellent crystallinity and stoichiometric composition shows less degradation. 7 It is also found that the morphology of BAM phosphor particles is also one of the contributors for degradation.…”
mentioning
confidence: 99%
“…According to Refs. [17,18], there are at least three different Eu 2+ sites named with BR, a-BR and mO sites, which have maximal emission at about 2.79 (445 nm), 2.61 (476 nm), and 2.43 eV (511 nm), respectively. Therefore, the change of Eu 2+ distribution in different sites will undoubtedly result in different features of emission spectra, such as peak position and full-width at half-maximum (FWHM), and then lead to different chromaticity coordinates.…”
Section: Luminescent Properties Before Annealingmentioning
confidence: 99%
“…However, its luminescence intensity is distinctly decreased by heat treatment during the manufacturing process. This deterioration is one of the most significant shortcomings in the application [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that thermal degradation of BAM occurs by oxidation of divalent Eu to its trivalent form due to the adsorbed oxygen atom diffused into the conduction layer accompanied by the oxygen vacancies, several possible interpretations regarding the detailed oxidation mechanism have been reported [5,6,8]. On the other hand, some studies suggested that the thermal degradation was due to a structural change such as an altered local environment for the Eu 2+ ions and the migration of Eu 2+ ions [7,9,10]. In our previous work, it has been confirmed that restricting the migration of Eu 2+ from mirror planes to spinel blocks is an efficient way to improve the thermal stability [11].…”
Section: Introductionmentioning
confidence: 99%